ANALISIS WAKTU PROSES PRODUKSI RANSEL BAGIAN SEWING DENGAN METODE LINE BALANCING PADA PERUSAHAAN GARMEN - Alloysius Vendhi Prasmoro; Helena Sitorus; Yovi Andiyana; Indrani Dharmayanti (Jurnal Riset Teknik Komputer, 2024)
The object of this research is companies operating in the garment industry which must compete with other garment companies. This research focuses on measuring the backpack production process time in the sewing section. Problems occur because production targets are not achieved, where a mismatch in the tasks assigned to workers causes an imbalance in the line which prevents the expected level of productivity from being achieved. This is because there is no standard time for each process and the track efficiency is not yet balanced. This research aims to determine the standard sewing time for line 1, determine the efficiency value of the initial line and maximize the line. The method used is Line Balancing Ranked Position Weight (RPW), a process time measurement method that prioritizes the longest work element time first to be placed on another work station which represents the lower work element time. Based on data analysis, it is known that the cycle time on the initial route is high and the line efficiency value is small with a total of 9 work stations. For this reason, the researchers made a proposed line by moving work elements and adding work stations to a total of 15 work stations. The conclusions of this research are (1) The cause of not achieving backpack bag production is because the cycle time is not balanced. (2) The initial standard time for line 1 sewing is 187.7 seconds. After improvements the standard time became 93.5 seconds. (3) Application of the Ranked Position Weight method produces a previous track efficiency of 60.32% and after improvements it is 72.67%. (4) Moving work elements results in better line balance and affects the level of worker productivity